Uso da lógica de programação no desenvolvimento de jogos para crianças do ensino fundamental: um caso de informática educativa na escola pública - SILVA, Sara das Mercês (2019)
Today's technological context calls for education to position itself in the face of major changes and the accelerated level of new information, the schools should not be left out of new technologies because education can gain in many ways from the insertion of Computing and all its resources. The way of teaching and acquiring knowledge has been evolving over the years and the changes brought about by the development of technology. The computer can contribute to the teaching-learning process, but not all schools have access to computational resources, just as the teaching of programming logic, although not in the current curriculum of basic education, can be applied in supervised work and activities with children and teenagers, contributing to the students' cognitive development. This work reports the use of the computer to teach programming logic to students of the elementary school Aristides Santa Rosa in Inhangapi (northeast of Pará) and during the classes an educational game was developed encouraging the preservation of the present river in the city. The work was driven by the need to arouse in students, interest in computing and the importance of sustainable practices, because the school is located in a city in the Amazon region. The built game was evaluated through the Fourface tool that identifies the user's emotional state. The results expressed in the paper are positive, because among the results in the tests it is emphasized that, 95% of the students expressed joy emotion when using the computer as a tool to encourage environmental preservation, 84% of children demonstrated basic knowledge about logic and 100% of students said they enjoy learning with game development.